Work ability as a risk marker of employee health and organisational effectiveness in four UK manufacturing organisations - Coomer, Karen (2017)
Work ability (WA) concerns a worker’s capacity to manage their job demands in relation to their physical and psychological resources. Over the last decade, the WA construct and its associated measurement instrument, the Work Ability Index (WAI), have become established within occupational health practice in several countries, particularly within Scandinavia. One consequence of this is that occupational health researchers have begun to utilise WA in the prediction of worker health and operational effectiveness outcomes.